Cardioversion of atrial fibrillation and atrial flutter revisited: current evidence and practical guidance for a common procedure. Issue 8 (26th April 2020) - Brandes, Axel; Crijns, Harry J G M; Rienstra, Michiel; Kirchhof, Paulus; Grove, Erik L; Pedersen, Kenneth Bruun; Van Gelder, Isabelle C
Abstract: Cardioversion is widely used in patients with atrial fibrillation (AF) and atrial flutter when a rhythm control strategy is pursued. We sought to summarize the current evidence on this important area of clinical management of patients with AF including electrical and pharmacological cardioversion, peri-procedural anticoagulation and thromboembolic complications, success rate, and risk factors for recurrence to give practical guidance.